Validated Hptlc Method For Simultaneous Estimation Of Thiocolchicoside And Aceclofenac In Bulk Drug And Formulation - SUNITA T. PATIL,; VIDHYA K. BHUSARI,; SUNIL R. DHANESHWAR, (International Journal of Pharma and Bio Sciences, 2011)
This paper describes a new, simple, precise, and accurate HPTLC method for simultaneous estimation of Thiocolchicoside and Aceclofenac as the bulk drug and in tablet dosage forms. Chromatographic separation of the drugs was performed on aluminum plates precoated with silica gel 60 F254 as the stationary phase and the solvent system consisted of toluene: ethyl acetate: methanol: glacial acetic acid (4: 6: 2: 0.5 v/v/v/v). Densitometric evaluation of the separated zones was performed at 255 nm. The two drugs were satisfactorily resolved with RF values 0.16 and 0.79 for Thiocolchicoside and Aceclofenac, respectively. The accuracy and reliability of the method was assessed by evaluation of linearity (6–21 ng/spot for Thiocolchicoside and 10-35 ng/spot for Aceclofenac), precision (intra-day RSD 0.31–1.01 % and inter-day RSD 0.51–0.72 % for Thiocolchicoside, and intra-day RSD 0.66–0.94 % and inter-day RSD 0.79–1.04 % for Aceclofenac), accuracy (100.30 ± 0.35 % for Thiocolchicoside and 99.48 ± 0.41 % for Aceclofenac), and specificity, in accordance with ICH guidelines.